Relasi Gender Suami Istri yang Bekerja (Studi Kasus pada Keluarga Pekerja di Transmart Padang) - Haniey Fauziah; Elva Ronaning Roem; Asmawi Asmawi (Prodi Pendidikan Sejarah Fakultas Keguruan dan Ilmu Pendidikan Universitas Islam Sumatera, 2023)
Working husbands and wives often spend limited time together, and some women work on shift-based schedules. However, the scarcity of family time does not pose a problem for these couples. Consequently, the significance of interpersonal communication in male-female relationships lies in establishing gender dynamics within the family. This study aims to elucidate gender communication patterns in working couples and identify a division of labor that fosters family harmony. Employing qualitative research methods and a case study approach, the study analyzes the data through the lens of relational dialectic theory. The findings reveal that interpersonal communication plays a pivotal role in male-female relationships, enabling gender dynamics to flourish even when women have better careers and higher incomes than their male partners. Consequently, husbands' roles in domestic life remain intact, as they actively support their wives' career choices.